Analysis of Growth Gracilaria sp. In Shrimp Pound From The Level of Sedimentation - Niniek Widyorini (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Due to the increasing of Gracilaria sp demand in international market, intensive culture is required for it. Used niche of shrimp pound could be give adventages in Gracilaria sp culture, and also Gracilaria sp culture in shrimps pound can be used as shelter for the shrimp from direct sunlight. The aim of this research are to know sedimentation effect in shrimp pound its relationship in Gracilaria sp growth and water quality because of existing Gracilaria sp in the pound.The research  on June until December 2005.Experiment research method is used in this research. Data of Gracilaria sp growth and level of sedimentation will be collected in 7 (seven) weeks in one week time interval “rakit apung” methods is used in this research and its located the near of water inlet, pound fields, and near the water outlet. Corelation and regration are used to data analysis. Temperature, salinity, pH, depth, water flow and transparency of the water will be analyzed for water quality. As the result, the average of growth level of Gracilaria sp which is located in the fields pound higher than Gracilaria which located both near the water inlet and outlet, and the average of sedimentation level in the field pound less than both near the water inlet and outlet. In corelation regretion analysis found an interaction between level of sedimentation and the growth of Gracilaria sp especially which is located near the water inlet. The water quality still good for Gracilaria sp.Key Words: Sedimentation, Gracilaria sp, Growth